Non-linear association between lactate and 28 days mortality in elderly patients with sepsis across different SOFA score groups: results from the eICU Collaborative Research Database - Lanlang Zhang; Huiwen Liu; Dan Zhang; Youyou Deng; Xinglin Chen; Luyang Zhang (Frontiers in Medicine)
PurposeThis study aimed to examine the correlation between lactate levels and 28 days mortality in elderly sepsis patients across different Sequential Organ Failure Assessment (SOFA) score groups following ICU admission.MethodsA multi-center retrospective cohort study utilized data from the eICU Collaborative Research Database, encompassing elderly sepsis patients from 208 ICUs across the United States during 2014–2015. Lactate levels and SOFA scores at admission were collected, with a focus on 28 days mortality post-ICU admission. A two-piece-wise linear regression model was developed to assess the threshold effects of lactate on outcomes and its variation across SOFA score categories. Smooth curve fitting was utilized.ResultsOf the 5,150 patients with a median age of 76 years, 711 (13.8%) died within 28 days of ICU admission. A positive correlation was noted between lactate levels and mortality when lactate was < 3.7 mmol/l, with an adjusted odds ratio (OR) of 1.33 (95% CI: 1.17–1.51, P < 0.0001) for each increment in lactate. For lactate levels ≥ 3.7 mmol/L, mortality increased with an adjusted OR of 1.11 (95% CI: 1.05–1.18, P = 0.0003) for each increment in lactate. Moreover, mortality was low and rose gradually with increasing lactate levels in the SOFA score ≤ 5 group. Conversely, in the SOFA score > 5 group, mortality increased significantly, particularly when lactate levels exceeded 5 mmol/L.ConclusionThis study reveals a non-linear positive relationship between lactate and 28 days mortality among elderly sepsis patients. Furthermore, stratification by SOFA score demonstrated that patients with higher scores exhibited a heightened risk of mortality as lactate levels increased.